Analysis of Affixation Use Errors in Argumentation Texts in Grade X Students of SMA Bina Putra, Tangerang Regency - Soibanissibti, M. (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research entitled (title) aims to describe students' mistakes in using affixation when creating text. Affixation errors are in the form of prefixes (prefixes), infixes (insertions), suffixes (endings), and confixes (combinations) contained in students' argumentative texts. This research was conducted because students still lack understanding about the correct use of affixation. This research uses a qualitative approach, descriptive methods and content analysis techniques. The data collected was the work of students in the form of argumentation texts for class. To analyze this work, this research used an instrument in the form of an affixation error analysis table. From the results of this analysis, there were 144 errors in the use of affixation. Based on the details, there were errors in prefixes (prefixes) in 54 words, suffixes (endings) in 3 words, confixes (combinations) in 57 words, and there were no errors in infixes (insertions). Mistakes occur as a result of students' lack of understanding of both the use of affixes and the vocabulary they have, so that their use is inaccurate and difficult to understand.